Adverse childhood experiences on internet gaming disorder mediated through insomnia in Chinese young people - Guo, Ningyuan; Weng, Xue; Zhao, Sheng Zhi; Zhang, Juan; Wang, Man Ping; Li, Li; Wang, Lin (Frontiers in Public Health, 2023)
Background Adverse childhood experiences (ACEs) have been associated with addictions such as substance use disorders. Few have examined ACEs on internet gaming disorder (IGD) as a newly established behavioral addiction, and the potential mediating role of insomnia remains unclear. We examined the associations between ACE number and types, IGD, and insomnia. Methods Participants included 1, 231 Chinese university students (54.5% male; 56.9% aged 18–20 years) who had played internet games at least once in the previous month. ACEs were measured using the 10-item ACE questionnaire (yes/no). Symptoms of insomnia and IGD were measured using the Insomnia Severity Index and the 9-item Internet Gaming Disorder Scale–Short-Form, respectively. Multivariable regressions examined the associations, adjusting for sex, age, maternal and paternal educational attainment, monthly household income, smoking, and alcohol drinking. The mediating role of insomnia symptoms was explored. Results The prevalence of ACEs≥1 was 40.0%. Childhood verbal abuse was the most prevalent (17.4%), followed by exposure to domestic violence (17.1%) and childhood physical abuse (15.5%). More ACE numbers showed an association with IGD symptoms (adjusted OR = 1.11, 95% CI 1.04, 1.17). Specifically, IGD symptoms were observed for childhood physical neglect, emotional neglect, sexual abuse, parental divorce or separation, and household substance abuse. Insomnia symptoms mediated the associations of ACE number and types with IGD symptoms (proportion of total effect mediated range 0.23–0.89). Conclusion The number and specific types of ACEs showed associations with IGD mediated through insomnia. Screening of ACEs is recommended in future studies on IGD. Longitudinal data are warranted to determine the causality of the observed associations.